PIGN prevents protein aggregation in the endoplasmic reticulum independently of its function in the GPI synthesis - Ihara, Shinji; Nakayama, Sohei; Murakami, Yoshiko; Suzuki, Emiko; Asakawa, Masayo; Kinoshita, Taroh; Sawa, Hitoshi (Journal of cell science, 2017)
Quality control of proteins in the endoplasmic reticulum (ER) is essential for ensuring the integrity of secretory proteins before their release into the extracellular space. Secretory proteins that fail to pass quality control form aggregates. Here we show the PIGN-1/PIGN is required for quality control in Caenorhabditis elegans and in mammalian cells. In C. elegans pign-1 mutants, several proteins fail to be secreted and instead form abnormal aggregation. PIGN-knockout HEK293 cells also showed similar protein aggregation. Although PIGN-1/PIGN is responsible for glycosylphosphatidylinositol (GPI)-anchor biosynthesis in the ER, certain mutations in C. elegans pign-1 caused protein aggregation in the ER without affecting GPI-anchor biosynthesis. These results show that PIGN-1/PIGN has a conserved and non-canonical function to prevent deleterious protein aggregation in the ER independently of the GPI-anchor biosynthesis. PIGN is a causative gene for some human diseases including multiple congenital seizure-related syndrome (MCAHS1). Two pign-1 mutations created by CRISPR/Cas9 that correspond to MCAHS1 also cause protein aggregation in the ER, implying that the dysfunction of the PIGN non-canonical function might affect symptoms of MCAHS1 and potentially those of other diseases.